Penguatan Literasi Digital melalui Pemanfaatan Aplikasi dan Situs Web Pembelajaran bagi Guru dan Siswa di SDN 1 Guntur Macan - Henni Comala Hikmi; Karina Nurwijayanti; Lalu Moh. Nurkholis; Emi Suryadi (BADAN PENERBIT STIEPARI PRESS, 2025)
Digital literacy is a crucial effort in preparing for the Society 5.0 era. By integrating technology with digital literacy, teachers are better equipped to deliver engaging, effective, and high-quality instruction to students who are growing up in a digital-centric environment. Digital literacy empowers students to participate actively in the learning process while fostering critical and creative thinking in utilizing available information. This Community Service aims to enhance the digital literacy of both teachers and students through the introduction and practical application of educational websites and digital tools. The program was implemented in collaboration with SDN 1 Guntur Macan, located in Gunung Sari, West Lombok. The activity involved 9 elementary school teachers and thirty students from grades V and VI. The methodology in this Community Service program consisted of interactive training sessions and hands-on practice with various digital platforms and applications. The program evaluation indicated a notable improvement in teachers' understanding of digital literacy concepts and the use of digital tools related to instruction. Furthermore, the initiative successfully increased teachers' motivation to integrate technology into classroom learning practices.